High incidence of pulmonary tuberculosis in an indigenous Saharia tribe in Madhya Pradesh, central India-A prospective cohort study. - Jyothi Bhat; Rajiv Yadav; Ravendra K Sharma; Malaisamy Muniyandi; V G Rao (Public Library of Science (PLoS), 2022)
Background Lack of TB incidence data is an important evidence gap among Saharia-a high TB burden indigenous community in Madhya Pradesh, central India. The present study was undertaken to calculate the incidence of pulmonary tuberculosis in this tribe. Objective To calculate the incidence of pulmonary tuberculosis (PTB) among the Saharia tribal population in Madhya Pradesh, central India. Methods A prospective cohort study was conducted among the Saharia tribal population (aged 15 years and above) of Shivpuri district in Madhya Pradesh state in central India. A total of 9,756 individuals were screened for TB in the baseline TB prevalence survey during 2012-13. All available household members were screened for symptoms suggestive of pulmonary TB (presumptive TB). Two sputum specimens were collected from persons having symptoms suggestive of TB and examined by smear and culture tests. A cohort of all non-TB individuals in the baseline survey was followed-up for one year and re-screened for the sysmptoms of PTB in the year 2014-15. Based on the data collected, the incidence of TB over one year period was estimated per 100,000 population. Results A total of 9756 and 9044 individuals (≥ 15 years) were screened for symptoms suggestive of PTB during baseline and endline surveys respectively. The sputum specimens of presumptive TB cases were collected and examined by smear and culture tests. The overall incidence of bacteriologically positive (smear and/or culture) PTB over one year period was 1504 (95% Confidence Interval (CI): 1273-1776) per 100,000 in the study population, the incidence of smear-positive PTB was 1106 (95% CI: 910-1343), and the incidence of culture-positive PTB was 1084 (95% CI: 890-1319) per 100,000 population. The incidence for both smear and culture-positive PTB was 686 (95% CI: 535-878) per 100,000 population in the year 2014-15. The incidence of PTB was 2.8 times higher in males compared to females (2259 vs 807 per 100,000) and was positively correlated with age. Conclusion The findings of the study, the first of its kind in the Saharia tribal population, indicate a high incidence of TB in this tribal community thereby highlighting the urgent need for focused and intensified efforts to achieve the goal of TB elimination in the country.